Mesoamerican Archaeology, Copies and Museums. Reflections on the Circulation of Santa Lucía Cotzumalguapa Casts - Gallipoli, Milena (2024)
This paper analyzes the production and exhibition of casts of Mesoamerican archaeology based on the case of Monument 21 of Santa Lucía Cotzumalguapa to reflect on the historical and current geopolitical relations derived from the circulation of originals and copies. The connections and parallel histories of, in principle, three objects are addressed: the original at the Bilbao site, the mold that was made in situ and transferred to Berlin so that a reproducible model could be made from the Staatlichen Museen, and, finally, a plaster cast that was acquired for Buenos Aires. The simultaneous exhibition of the objectual universe of Monument 21 allows us to reflect on the exhibition complexes and their reconfigurations in a panorama informed by debates on the colonial past.